Rules of origin - Kapeleta, Chimvano Humphreys (KDI School, 2011)
The Common Market for Eastern and Southern Africa (COMESA), Southern African Development Community (SADC), and the East African Community (EAC), are just three of so many Regional Economic Communities (RECs) on the African continent. Together, the three RECs have a combined membership of twenty-six countries, stretching from South Africa in Southern Africa to Egypt in North Africa. One of the main challenges facing COMESA, EAC and SADC in the implementation of their integration programs is the overlapping membership of their respective Member States. For instance, EAC is already a Common Market but it shares four Member States with COMESA which is a Customs Union, and one Member State with SADC which is a Free Trade Area. On the other hand, SADC and COMESA have seven member states in common; while five of the SADC Member States are also members of Southern African Customs Union (SACU). Partly to rectify this anomaly, and partly to contribute towards the goal of achieving the African Economic Community as stipulated in the Abuja Treaty of 1991, the three RECs have recognized the need to initiate a process of coordination and harmonization of their regional integration programs. In that regard, the three have agreed to form one grand Free Trade Area, possibly by 2012, a decision that was endorsed by the Heads of State and Government of the twenty-six countries that comprise the three regional institutions in October 2008. Already, COMESA, EAC and SADC have made significant progress in simplification of customs procedures and documentation; rationalization of the COMESA and SADC customs bond guarantee schemes; development of customs training and capacity building schemes; preparation of an inventory of harmonized product standards; co-ordination of competition policies and institutional frameworks; identification, removal and monitoring of non-tariff barriers; as well as establishment of One-Stop Border Posts. This thesis holds that the differences in the Rules of Origin that govern trade regimes in the three RECs will be the biggest huddle towards realization of the grand Free Trade Area. More to the point, the forces that necessitated the complicated and restrictive SADC Rules of Origin are still at work even now when the official negotiations for the grand FTA have been launched. Unless some countries in the two regions, notably South Africa, and to some extent, Egypt, show some flexibility in the way they protect their vested interests, especially by using Rules of Origin, the idea of a Free Trade Area extending from Cape to Cairo will remain just a dream.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: SADC--COMESA--EAC